Neuroprotective effects of four different fluids on cerebral ischaemia/reperfusion injury in rats through stabilization of the blood–brain barrier. (26th July 2021) - Shan, Reai; Zhou, Hongyan; Liu, Xinfang; Su, Guangjun; Liu, Guangsen; Zhang, Xiaoli; Sun, Cong; Yu, Zining; Zhan, Lifang; Huang, Zhihua
Abstract: Protecting the blood–brain barrier (BBB) is a potential strategy to treat cerebral ischaemic injury. We previously reported that hypertonic sodium chloride hydroxyethyl starch 40 (HSH) treatment alleviates brain injury induced by transient middle cerebral artery occlusion (tMCAO). However, other fluids, including 20% mannitol (MN), 3% hypertonic sodium chloride (HTS) and hydroxyethyl starch 130/0.4 solution (HES), have the same effect as HSH in cerebral ischaemia/reperfusion injury (CI/RI) remains unclear. The present study evaluated the protective effects of these four fluids on the BBB in tMCAO rats. Sprague–Dawley (SD) rats were randomly assigned to six groups. A CI/RI rat model was established by tMCAO for 120 min followed by 24 h of reperfusion. The sham and tMCAO groups were treated with normal saline (NS), whereas the other four groups were treated with the four fluids. After 24 h of reperfusion, neurological function, brain oedema, brain infarction volume, permeability of the BBB, cortical neuron loss and protein and mRNA expression were assessed. The four fluids (especially HSH) alleviated neurological deficits and decreased the infarction volume, brain oedema, BBB permeability and cortical neuron loss induced by tMCAO. The expression levels of GFAP, IL‐1β, TNF‐α, MMP‐9, MMP‐3, AQP4, MMP‐9, PDGFR‐β and RGS5 were decreased, whereas the expression levels of laminin and claudin‐5 were increased. These data suggested that small‐volume reperfusion using HSH, HES, MN and HTS ameliorated CI/RI, probably by attenuating BBB disruption and postischaemic inflammation, with HSH exerting the strongest neuroprotective effect. Abstract : The four different liquids treatment inhibits the activation of astrocyte and pericyte and increases the expression of tight junction proteins and then stabilizes BBB and protects neurons in tMCAO rats.